The impact of philosophy and concepts of logic in Abbasid poetry (Journal of the College of Basic Education, 2022)
Through serious research, it was confirmed to us that what affects nature affects human life alike. Change is permanent and continuous, and it is a natural phenomenon that emerged from the struggle of opposites among them. Without it, nothing would move and change, because stability is death and movement is life, and the best witness and evidence is the protest of a bold group, Reasonable over the happiness of the gods and the misery of mankind, and justice must be achieved, to make everyone happy, and that the relationship should not be a slave-to-hand relationship, without a relationship of participation in destiny, despite religious extremism and the worship of gods is not believed to be killed, but the conflict of opposites is the reason for that, and there are also two forces Two influences in human life: They are the power of love, through which peace, happiness, tranquility and brotherhood are achieved, and the power of hatred: the source of all evil, chaos, turmoil, disorder, and misery, and then if falsehood has authority, then truth has authority, and this is what was achieved after the abolition of multiple gods and their worship and belief in one God. The criterion of science and the correct approach with its logical measures for choosing vocabulary and terminology with high accuracy to accommodate the meanings to be achieved. Without it, the literary and theatrical criticism movement would not have flourished in Greece in particular and the world in general, as it is the guiding compass for the pioneers of science and critics to take its methods and logical measures as tools of scientific, academic, objective criticism, correct evaluation and fair arbitration. After criticism was individual, subjective, emotional, far from objectivity and the spirit of science.